Evolutionary insight into South African freshwater crabs (Potamonautes) based on genetics and morphometrics - Gunkel, Kallyn Graham Roger (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.